2011
DOI: 10.1194/jlr.m014647
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 controls lipolysis in adipocytes via FOXO1-mediated expression of ATGL

Abstract: unhealthy levels of circulating FFAs requires the tight control of lipolysis.It is now appreciated that lipolysis is a complicated multi-step process. The complete hydrolysis of TG to glycerol and FFA is performed jointly by tri-di-and monoacylglyceride lipases ( 7-9 ). The recently discovered enzyme adipose triglyceride lipase, or ATGL (a.k.a. desnutrin, PNPLA2, TTS2.2, iPLA 2 ) ( 10-12 ) is responsible for the bulk of triacylglycerol hydrolase activity in various cells but has low affi nity to di-and monoacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(106 citation statements)
references
References 64 publications
5
101
0
Order By: Relevance
“…SIRT1 promotes lipolysis in adipocytes via activation of the rate-limiting lipolytic enzyme ATGL [14]. Here, we found that exenatide (exendin-4) reduced adiposity by activating SIRT1 and consequently upregulating ATGL.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…SIRT1 promotes lipolysis in adipocytes via activation of the rate-limiting lipolytic enzyme ATGL [14]. Here, we found that exenatide (exendin-4) reduced adiposity by activating SIRT1 and consequently upregulating ATGL.…”
Section: Discussionmentioning
confidence: 56%
“…Increased SIRT1 activity leads to the activation of adipose triacylglycerol lipase (ATGL), with subsequent triacylglycerol depletion of WAT [14]. Moreover, overexpression of SIRT1 in WAT effected a reduction of fat accumulation in adipocytes, with improved whole-body energy expenditure [15].…”
Section: Introductionmentioning
confidence: 99%
“…FOXOs are typically associated with the transcription of genes downstream to insulin/insulin-like growth factor (IGF) signaling, which include lipogenic and lipolytic genes (14, 15). Although SIRT1 regulates FOXO-dependent transcription (16), the importance of the SIRT1-FOXO cross talk in mediating the effects of insulin signaling at the organismal level is poorly addressed (17)(18)(19). In this respect, it is important to delineate the Sir2/SIRT1-dependent fat phenotype from insulin resistance in the liver and in peripheral tissues (muscles), in addition to investigating the role of FOXO in regulating these effects.…”
mentioning
confidence: 99%
“…SIRT1 is induced in several tissues during CR (18) and responds to the organism's need for energy by stimulating lipid breakdown through the transcription factor FoxO1, which directly induces expression of the rate-limiting lipolytic enzyme adipose triglyceride lipase (19). SIRT1 also inhibits cells' ability to synthesize fat by deacetylating the lipogenic activator SREBP-1c, preventing this factor from binding the promoters of lipogenic genes (20,21).…”
Section: Metabolismmentioning
confidence: 99%